2017
DOI: 10.1080/03079457.2017.1325442
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein, haematologic and blood chemistry changes in African grey parrots (Psittacus erithacus) experimentally infected with bornavirus

Abstract: Bornaviruses are considered to be the causative agent of proventricular dilatation disease (PDD) in psittacine birds. In order to detect haematological and blood chemistry changes during the development of PDD and a possible correlation with clinical signs and the virological status, six African grey parrots (Psittacus erithacus) were experimentally infected with parrot bornavirus 4 (PaBV-4) by subcutaneous route. All six parrots developed clinical signs of varying extent and successful infection was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…51 Thus far, these types of changes have been reported mostly in avian samples with infectious processes. [52][53][54][55][56][57][58][59][60] An abnormal electrophoretogram, therefore, can demonstrate the presence of an acute-phase response but is not supportive of the presence of any one specific disease. The exception is the presence of paraproteinemia, which is most commonly observed with lymphoproliferative diseases and some infectious diseases; the latter is primarily described in mammals.…”
Section: Detection Of Hyperglobulinemias For Added Valuementioning
confidence: 99%
See 1 more Smart Citation
“…51 Thus far, these types of changes have been reported mostly in avian samples with infectious processes. [52][53][54][55][56][57][58][59][60] An abnormal electrophoretogram, therefore, can demonstrate the presence of an acute-phase response but is not supportive of the presence of any one specific disease. The exception is the presence of paraproteinemia, which is most commonly observed with lymphoproliferative diseases and some infectious diseases; the latter is primarily described in mammals.…”
Section: Detection Of Hyperglobulinemias For Added Valuementioning
confidence: 99%
“…113 EPH has been used as an adjunct tool in the diagnosis of infectious diseases, including chlamydiosis, aspergillosis, sarcocystosis, bornavirus infection, and mycobacteriosis. [52][53][54][55][56][57][58][59][60]64 In a study of African penguins with presumed or confirmed aspergillosis, a significant increase in alpha 2 globulins was associated with a specificity of 92% and a negative predictive value of 81%. In conjunction with increases in beta globulins and 3-hydroxybutyrate, the specificity was 98%.…”
Section: Avian S Pecie Smentioning
confidence: 99%
“…Other changes such as leukocytosis and heterophilia have been inconsistently reported in some patients and may be associated with stress and secondary infections [20]. These findings have been supported by experimental studies [37]. Although the bloodwork of patients suffering from PDD might not indicate any definitive indication of the infection, it is advisable to perform hematology and clinical chemistry assessments of suspected patients to rule out differential diagnoses and to assess their general health.…”
Section: Clinical Pathology and Serologymentioning
confidence: 97%
“…Birds suffering from PDD show inconsistent changes in hematology and clinical chemistry assessments, and most are usually related to the catabolic state induced by gastrointestinal malabsorption, such as nonregenerative anemia and decreased total protein and albumin levels [ 20 , 37 ]. Additionally, elevated levels of muscle enzymes such as lactate dehydrogenase, creatine kinase and aspartate aminotransferase may be seen in infected birds.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation